The THE ROLE OF PARENTS IN THE EDUCATION OF CHILDREN WITH SPECIAL NEEDS AT TK DHARMA MELONGUANE, TALAUD ISLANDS DISTRICT - Tewuh, Adeleida (International Conferences on Early Childhood Education Proceedings, 2024)
The role of parents is one of the determining factors for the success or failure of children in the educational process. Parents play a crucial role in supporting their children's education as well as their growth and development. The success of children heavily depends on their parents and the surrounding environment. This is particularly true for children with special needs, who have unique potential and abilities compared to their peers but should still receive equal treatment and opportunities. Parental involvement in the learning process is crucial to create effective learning environments for children. This research aims to examine the role of parents in the education of children with special needs. The research utilized a survey method, and the findings indicate that the role of parents in the education of children with special needs at TK Dharma Melonguane, Talaud Islands District, falls into the low category, with 20% or 3 out of 15 parents involved in their child's education. Keywords: Parental Role, Children with Special Needs.